Gastrointestinal Autonomic Neuropathy Exacerbates Gut Microbiota Dysbiosis in Adult Patients With Type 2 Diabetes Mellitus - Du, Yuhui; Neng, Qiongli; Li, Yu; Kang, Yongbo; Guo, Liqiong; Huang, Xinwei; Chen, Minghui; Yang, Fan; Hong, Jingan; Zhou, Shuai; Zhao, Jianhua; Yu, Fubing; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Objective: The diabetic autonomic neuropathy is one of the most common chronic complications in diabetes, especially gastrointestinal autonomic neuropathy (GAN), which may occur in up to 75% of patients. The study aimed to investigate the gut microbiota composition, structure, and function in adult patients with T2DM with gastrointestinal autonomic neuropathy (T2DM_GAN) and set up a link between microbiological functions and or patients’ clinical data. Methods: DNA was extracted from fecal samples of three groups using the kit method: healthy volunteers (n=19), the patients with T2DM (n=76) and T2DM_GAN (n=27). Sequencing of 16S ribosomal DNA was performed using the MiSeq platform. Results: According to the clinical data, higher AGE, lower TG and lower BMI were the main features of patients with T2DM_GAN. The gut microbiota analysis showed that Bacteroidetes, Firmicutes, and Proteobacteria constituted the three dominant phyla in all samples. GAN exacerbates gut microbiota dysbiosis in adult patients with T2DM. And 29 KEGG pathways in T2DM_GAN patients were altered as compare T2DM patients. In addition, T2DM patients were characterized by phylum Fusobacteria, class Fusobacteriia, order Fusobacteriales, family Fusobacteriaceae, genus Fusobacterium, genus Lachnoclostridium and species Fusobacterium_mortiferum. Those gut microbiota were significantly positive correlation with Carotenoid biosynthesis and Flavonoid biosynthesis. In contrast, the class Gammaproteobacteria, order Enterobacteriales, family Enterobacteriaceae, genus Escherichia-Shigella, genus Megasphaera, species Escherichia_coli, species Megasphaera_elsdenii and others were characteristic in the T2DM_GAN patients. And those were significantly positive correlation with Bacterial invasion of epithelial cells and Pathogenic Escherichia coli infection. Conclusions: Both the phyla Fusobacteria and class Gammaproteobacteria and their members or functions related to them were closely related to the occurrence of T2DM. Especially the latter, may promote complications related to gastrointestinal symptoms, such as T2DM_GAN.